Hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material and preparation method and application thereof

CN116585535BActive Publication Date: 2026-11-03SOUTH CHINA UNIV OF TECH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310523168.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-10
Publication Date
2026-11-03
Estimated Expiration
2043-05-10

AI Technical Summary

Technical Problem

Existing bioactive glass bone repair materials have shortcomings in terms of molding and porous structure, which limits their application in bone tissue regeneration and repair.

Method used

Hyaluronic acid was functionally modified through amidation and click chemistry to construct hyaluronic acid derivatives, which were then combined with thiol-modified polyethylene glycol and bioactive glass. A hyaluronic acid/polyethylene glycol/bioactive glass composite hydrogel was prepared by rapid photocrosslinking reaction, and finally, a porous bone repair material was obtained by freeze-drying.

Benefits of technology

Rapid prototyping and interconnected hierarchical porous structures were achieved, promoting the biocompatibility and osteogenic activity of bone repair materials and supporting the regeneration and repair of bone tissue defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116585535B_ABST
    Figure CN116585535B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of biomedical materials, and particularly relates to a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material and a preparation method thereof. The present application constructs a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material with good biocompatibility, osteogenesis activity and porous structure, and proposes a method for rapidly preparing the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material through light cross-linking, so as to solve the problems of insufficient osteogenesis activity and porous structure of the bone repair material, and the method can be applied to the regeneration and repair of bone tissue defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of biomedical materials, and in particular to a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material and its preparation method. Background Technology

[0002] To achieve bone regeneration and repair caused by trauma, bone tumors, and other factors, the intervention of biomedical materials is often required. Biomedical materials with good biocompatibility, bone-activating properties, and porous structures are preferred for bone defect regeneration and repair.

[0003] Bioactive glass materials are a class of biodegradable bioactive materials that promote osteogenic and angiogenesis. They can continuously release active ions such as silicon, calcium, and phosphorus to promote the expression of osteogenic genes and regulate immune processes, thereby achieving bone defect regeneration and repair, and have significant clinical application value. Currently, widely used bioactive glass bone repair products (such as GuGeSheng and BeiGeSheng) are available in pure granule and putty formulations. However, these products have drawbacks such as difficulty in molding and easy collapse after filling, hindering their clinical application as bioactive materials for bone tissue regeneration and repair. Summary of the Invention

[0004] In view of this, the purpose of this invention is to overcome the shortcomings and deficiencies of the prior art, and to construct a porous bone repair material of hyaluronic acid / polyethylene glycol / bioactive glass with good biocompatibility, promoting bone activity, and porous structure. Furthermore, a method for rapidly photocrosslinking to prepare porous bone repair material of hyaluronic acid / polyethylene glycol / bioactive glass is proposed, which solves the problems of insufficient bone activity and porous structure in bone repair materials, and can be applied to the regeneration and repair of bone tissue defects.

[0005] It should be noted that, in order to endow bioactive glass materials with plasticity and achieve a porous structure, this invention constructs a porous bone repair material with good biocompatibility and high bone-promoting activity. This invention functionally modifies natural high-molecular-weight hyaluronic acid through amidation and click chemistry reactions to obtain hyaluronic acid derivatives capable of rapid photocrosslinking. Furthermore, a photocrosslinking gelation system is constructed using the hyaluronic acid derivative, bioactive glass, thiol-modified polyethylene glycol, and a photoinitiator. A hyaluronic acid / polyethylene glycol / bioactive glass composite hydrogel is prepared through a rapid photocrosslinking reaction. Finally, a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material is obtained using freeze-drying technology. This composite porous material possesses rapid molding characteristics, interconnected hierarchical pore characteristics, and bone-promoting angiogenesis characteristics, solving the problems of insufficient bone-promoting activity and porous structure in bone repair materials, and can be applied to the regeneration and repair of bone tissue defects.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A method for preparing a porous bone repair material composed of hyaluronic acid / polyethylene glycol / bioactive glass, specifically including the following steps:

[0008] S1 dissolves sodium hyaluronate in a carboxyl-activated solution, adds 2-furanylamine and maleimide at room temperature in the dark, reacts for 24 hours with stirring, dialyzes through a dialysis bag for 72 hours, and freeze-dries to obtain a hyaluronic acid derivative.

[0009] S2 dissolves hyaluronic acid derivatives, thiol-modified polyethylene glycol, bioactive glass, and photoinitiator in pure water to obtain a hydrogel precursor solution.

[0010] S3 transfers the precursor solution into a mold and exposes it to ultraviolet light to obtain a hyaluronic acid / polyethylene glycol / bioactive glass composite hydrogel.

[0011] S4 pre-freezes the obtained composite hydrogel in a refrigerator, and then freeze-dries it to obtain a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material.

[0012] Optionally, the sodium hyaluronate powder has a molecular weight of 1000-2500 kDa and is added at a concentration of 1-3% (m / v), that is, 1-3 g of hyaluronic acid is contained in every 100 ml of carboxyl-activated solution.

[0013] Further, the carboxyl-activating solution is a mixed aqueous solution of 4-(4,6-dimethoxytriazine)-4-methylmorpholine hydrochloride (DMTMM) and morpholine ethanesulfonic acid (MES), with a molar ratio of DMTMM to MES of 1:2 to 4. The molar ratio of the carboxylic acid groups in sodium hyaluronate to DMTMM is 1:3 to 5.

[0014] Furthermore, the molar ratio of carboxylic acid groups to 2-furanylamine molecules in sodium hyaluronate is 1:2 to 5, and the molar ratio of 2-furanylamine molecules to maleimide molecules is 1:1.

[0015] Furthermore, the molecular weight cutoff of the dialysis bag in step S1 is 8-14 kDa.

[0016] Optionally, the concentration of the hyaluronic acid derivative is 1-3% (m / v), that is, 1-3g of hyaluronic acid derivative is contained in every 100ml of solution.

[0017] Furthermore, the thiol-modified polyethylene glycol is a four-arm polyethylene glycol with thiol-modified end groups, having a molecular weight of 1-3 kDa, wherein the molar ratio of the thiol group to the carboxylic acid group contained in the hyaluronic acid derivative is 1:1-2.

[0018] Furthermore, the bioactive glass in step S2 is a sol-gel bioactive glass, composed of SiO2 (45-65%), CaO (25-35%), P2O5 (5-10%), and SrO (0-5%), with a surface area of ​​50-150 m². 2 / g, and its addition amount is 1-5% (m / v).

[0019] Furthermore, the photoinitiator in step S2 is one or more of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (I2959) and phenyl-2,4,6-trimethylbenzoyl lithium phosphine (LAP), and the amount added is such that the molar ratio of the photoinitiator molecule to the carboxylic acid group contained in the hyaluronic acid derivative is 1:5 to 15.

[0020] Optionally, the ultraviolet light in step S3 has a wavelength of 365 nm and an intensity of 15–30 mW / cm². 2 The illumination time is 1 to 30 seconds.

[0021] Optionally, the pre-freezing temperature in step S4 is -20 to -80°C, and the pre-freezing time is 24 to 48 hours.

[0022] As can be seen from the above technical solution, compared with the prior art, the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material, its preparation method, and its application provided by the present invention have the following superior effects:

[0023] This invention is scientifically designed, simple to prepare, and suitable for mass production. It utilizes amidation and click chemistry reactions to functionally modify natural high-molecular-weight sodium hyaluronate, obtaining hyaluronic acid derivatives capable of photocrosslinking. Further, a rapid photocrosslinking reaction is used to obtain a hyaluronic acid / polyethylene glycol / bioactive glass composite hydrogel. The preparation process is simple and controllable, with a fast reaction rate (gel formation within 1 second of light exposure). Furthermore, the porous bone repair material obtained after freeze-drying possesses an interconnected porous structure that facilitates the supply of nutrients both inside and outside the material, promotes cell migration from the outside to the inside of the material, and facilitates the continuous release of active ions such as silicon, calcium, and phosphorus from the bioactive glass material, thus promoting bone angiogenesis and aiding in the regeneration and repair of bone defects. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0025] Figure 1 This is a schematic diagram illustrating the preparation principle of the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material of the present invention.

[0026] Figure 2 Image of a lyophilized porous bone repair material made of hyaluronic acid / polyethylene glycol / bioactive glass.

[0027] Figure 3 This image shows the live-dead staining results of BMSCs cultured in porous bone repair material for 24 hours.

[0028] Figure 4 Scanning electron microscope image of a porous bone repair material made of hyaluronic acid / polyethylene glycol / bioactive glass. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] This invention discloses a method for preparing a porous bone repair material composed of hyaluronic acid, polyethylene glycol, and bioactive glass.

[0031] To better understand the present invention, the following embodiments are provided for further detailed description of the present invention, but they should not be construed as limiting the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above-described invention are also considered to fall within the protection scope of the present invention.

[0032] The technical solution of the present invention will be further described below with reference to specific embodiments.

[0033] Example 1

[0034] A method for preparing a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material includes the following steps:

[0035] S1: Weigh 10.27g of DMTMM and 15.86g of MES and add them to 900ml of pure water. Stir until completely dissolved to obtain a carboxyl-activated solution. Weigh 3g of sodium hyaluronate and add it to the carboxyl-activated solution. Stir until the sodium hyaluronate is completely dissolved to obtain an aqueous solution of sodium hyaluronate. Under light-protected conditions, add 1.44g of 2-furanylamine and 1.44g of maleimide to the aqueous solution of sodium hyaluronate and stir for 24 hours. Dialyze the solution using a dialysis bag with a molecular weight cutoff of 8-14kDa for 72 hours. After freeze-drying, obtain a hyaluronic acid derivative.

[0036] S2 weigh 3g of hyaluronic acid derivative, 2.79g of tetra-arm polyethylene glycol (molecular weight 1-3kDa) with thiol-modified end groups, 27g of bioactive glass (58S), and 0.33g of photoinitiator I2959, and dissolve them in 900ml of pure water to obtain the hydrogel precursor solution.

[0037] S3 transfers the precursor solution into a φ10x4mm mold, using a wavelength of 365nm and an intensity of 30mW / cm². 2 Irradiation with ultraviolet light for 10 seconds yields a hyaluronic acid / polyethylene glycol / bioactive glass composite hydrogel.

[0038] S4 pre-frozen the obtained composite hydrogel in a -20°C freezer, and then freeze-dried it to obtain a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material.

[0039] Its preparation principle is as follows Figure 1 As shown, a composite hydrogel was obtained by photocrosslinking between the prepared hyaluronic acid derivative and the thiol groups of the four-arm polyethylene glycol end groups, and a porous bone repair material was obtained by freeze-drying.

[0040] Example 2

[0041] A method for preparing a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material includes the following steps:

[0042] S1: Weigh 6.16g of DMTMM and 19.03g of MES and add them to 900ml of pure water. Stir until completely dissolved to obtain a carboxyl-activated solution. Weigh 3g of sodium hyaluronate and add it to the carboxyl-activated solution. Stir until the sodium hyaluronate is completely dissolved to obtain an aqueous solution of sodium hyaluronate. Under light-protected conditions, add 3.61g of 2-furanylamine and 3.61g of maleimide to the aqueous solution of sodium hyaluronate and stir for 24 hours. Dialyze the solution using a dialysis bag with a molecular weight cutoff of 8-14kDa for 72 hours. After freeze-drying, obtain a hyaluronic acid derivative.

[0043] S2 weigh 3g of hyaluronic acid derivative, 1.86g of tetra-arm polyethylene glycol (molecular weight 1-3kDa) with thiol-modified end groups, 9g of bioactive glass (58S), and 0.44g of photoinitiator LAP, and dissolve them in 900ml of pure water to obtain the hydrogel precursor solution.

[0044] S3 transfers the precursor solution into a φ10x4mm mold, using a wavelength of 365nm and an intensity of 15mW / cm². 2 Irradiation with ultraviolet light for 30 seconds yields a hyaluronic acid / polyethylene glycol / bioactive glass composite hydrogel.

[0045] S4 pre-frozen the obtained composite hydrogel in a -20°C freezer, and then freeze-dried it to obtain a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material.

[0046] The obtained freeze-dried hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material, such as Figure 2 As shown. The live-dead staining results of bone marrow mesenchymal stem cells (BMSCs) cultured for 24 hours in hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material are as follows. Figure 3 As shown.

[0047] Example 3

[0048] A method for preparing a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material includes the following steps:

[0049] S1: Weigh 8.22g of DMTMM and 19.03g of MES and add them to 900ml of pure water. Stir until completely dissolved to obtain a carboxyl-activated solution. Weigh 3g of sodium hyaluronate and add it to the carboxyl-activated solution. Stir until the sodium hyaluronate is completely dissolved to obtain an aqueous solution of sodium hyaluronate. Under light-protected conditions, add 2.16g of 2-furanylamine and 2.16g of maleimide to the aqueous solution of sodium hyaluronate and stir for 24 hours. Dialyze the solution using a dialysis bag with a molecular weight cutoff of 8-14kDa for 72 hours. After freeze-drying, obtain a hyaluronic acid derivative.

[0050] S2: Weigh 3g of hyaluronic acid derivative, 0.93g of tetra-arm polyethylene glycol (molecular weight 1-3kDa) with thiol-modified end groups, 9g of bioactive glass (58S), and 0.44g of photoinitiator LAP, and dissolve them in 900ml of pure water to obtain the hydrogel precursor solution.

[0051] S3 transfers the precursor solution into a φ10x4mm mold, using a wavelength of 365nm and an intensity of 15mW / cm². 2 Irradiation with ultraviolet light for 10 seconds yields a hyaluronic acid / polyethylene glycol / bioactive glass composite hydrogel.

[0052] S4 pre-frozen the obtained composite hydrogel in a -20°C freezer, and then freeze-dried it to obtain a hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material.

[0053] The obtained hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material has a porous structure such as Figure 4 As shown.

[0054] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a porous bone repair material of hyaluronic acid / polyethylene glycol / bioactive glass, characterized in that, Includes the following steps: S1 dissolves sodium hyaluronate powder in a carboxyl activation solution, adds 2-furanylamine and maleimide at room temperature in the dark, stirs and reacts for 24 hours, dialyzes for 72 hours, and then freeze-dries to obtain hyaluronic acid derivatives; S2 dissolves the hyaluronic acid derivative, thiol-modified polyethylene glycol, bioactive glass, and photoinitiator in pure water to obtain a hydrogel precursor solution; S3. The hydrogel precursor solution is transferred into a mold and irradiated with ultraviolet light to obtain a hyaluronic acid / polyethylene glycol / bioactive glass composite hydrogel. S4 pre-freezes the obtained composite hydrogel, then freezes it to obtain the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material. The carboxyl activation solution is a mixed aqueous solution of 4-(4,6-dimethoxytriazine)-4-methylmorpholine hydrochloride (DMTMM) and morpholine ethanesulfonic acid (MES), with a molar ratio of DMTMM to MES of 1:2~4. The bioactive glass is a sol-gel bioactive glass, and its composition, by mass percentage, consists of the following substances: SiO245~65%, CaO 25~35%, P2O55~10%, SrO 0~5%, Furthermore, the surface area of ​​the bioactive glass is 50~150 m². 2 / g; The thiol-modified polyethylene glycol is a four-arm polyethylene glycol with thiol-modified terminal groups and a molecular weight of 1~3 kDa.

2. The preparation method of the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material according to claim 1, characterized in that, The sodium hyaluronate powder has a molecular weight of 1000~2500kDa and is added at a concentration of 1~3% (m / v); the molar ratio of the carboxylic acid group in sodium hyaluronate to DMTMM is 1:3~5, the molar ratio of the carboxylic acid group in sodium hyaluronate to 2-furanylamine is 1:2~5, and the molar ratio of 2-furanylamine to maleimide is 1:

1.

3. The preparation method of the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material according to claim 1 or 2, characterized in that, In step S1, the molecular weight cutoff for dialysis is 8-14 kDa.

4. The preparation method of the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material according to claim 1, characterized in that, The concentration of the hyaluronic acid derivative is 1-3% (m / v), and the molar ratio of the thiol group to the carboxylic acid group contained in the hyaluronic acid derivative is 1:1-2.

5. The preparation method of the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material according to claim 1 or 4, characterized in that, The amount of bioactive glass added is 1~5% (m / v).

6. The preparation method of the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material according to claim 5, characterized in that, The photoinitiator is at least one of 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (I2959) and lithium phenyl-2,4,6-trimethylbenzoylphosphinic acid (LAP), and the molar ratio of the carboxylic acid groups contained in the photoinitiator and the hyaluronic acid derivative is 1:5~15.

7. The preparation method of the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material according to claim 1, characterized in that, In step S3, the ultraviolet light wavelength is 365 nm and the intensity is 15~30 mW / cm. 2 The illumination time is 1~30s.

8. The preparation method of the hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material according to claim 1, characterized in that, In step S4, the pre-freezing temperature is -20 to -80°C, and the pre-freezing time is 24 to 48 hours.

9. A porous bone repair material of hyaluronic acid / polyethylene glycol / bioactive glass prepared by the method described in claim 1, characterized in that, The hyaluronic acid / polyethylene glycol / bioactive glass porous bone repair material has a three-dimensional interconnected porous structure with a porosity of not less than 60% and a macropore size of 100~200 μm.

Citation Information

Patent Citations

  • Vascularized tissue-engineered bone constructed based on porous hydrogel material and application of vascularized tissue-engineered bone

    CN115702951A

  • Injectable bone constructed based on injectable hydrogel scaffold material and application of injectable bone

    CN115702952A